Comparison of Intralesional Triamcinolone and Intralesional Verapamil in The Treatment of Keloids: Triamcinolone vs Verapamil in Keloid Treatment - Batool, Asma; Akhtar, Aliya; Tahir, Sidra; Akhtar, Zahra; Batool, Amra; Iqbal, Shoaib (Pakistan Journal of Health Sciences, 2025)
An imbalance between synthesis and degradation of collagen and the extracellular matrix leads to keloid formation. Inadequately treated keloids lead to significant physical and emotional distress. Objectives: To compare the mean reduction of the Vancouver Scar score in patients with keloids after 3 months of treatment with intralesional triamcinolone versus intralesional verapamil. Methods: This parallel‐group, single‐blind randomized controlled trial was performed at the dermatology department, Nishtar Hospital, Multan, from April 2025 to September 2025. Sixty patients aged 10–50 years with keloids (1–5 cm, duration <5 years, baseline Vancouver score ≥5) were enrolled. Exclusion criteria were pregnant and lactating women, positive family history of keloids, conditions of acromegaly, and congestive heart illnesses. Group A (n=30) received intralesional verapamil monthly, and Group B (n=30) received intralesional triamcinolone acetonide (40 mg) monthly until keloid flattening or for three months. Vancouver scores were assessed at 16 weeks (four weeks post-treatment), and data were analyzed using SPSS version 23.0. Mean ± SD was recorded for quantitative and frequencies and percentages for categorical data. An independent sample t-test was used for numerical comparison at 5% significance level. Results: The mean age was 28.6±7.9 years with 58.3% males. The baseline Vancouver score was 8.7 ± 1.7, improving to 4.9 ± 1.5 after treatment. The triamcinolone group had a lower score (4.0 ± 0.7) and greater reduction (4.6±1.2) than the verapamil group (5.9 ± 1.5; reduction 2.9 ± 0.8; p<0.001). Conclusions: Overall, intralesional triamcinolone acetonide is clearly more effective than verapamil in reducing keloid severity.